Inhalation of nebulized Mycobacterium vaccae can protect against allergic bronchial asthma in mice by regulating the TGF-β/Smad signal transduction pathway - Xiao-hong Jiang; Chao-qian Li; Guang-yi Feng; Ming-jie Luo; Qi-xiang Sun (Allergy, Asthma & Clinical Immunology, 2020)
Abstract Background Mycobacterium vaccae nebulization imparted protective effect against allergic asthma in a mouse model. The TGF-β/Smad signal transduction pathway plays an important role in allergic bronchial asthma. However, the effect of M. vaccae nebulization on the TGF-β/Smad signal transduction pathway in mouse models of allergic asthma remains unclear. This study investigated the preventive effect of M. vaccae nebulization during bronchial asthma in a mouse model and elucidate the implication of TGF-β/Smad signal transduction pathway in the process. Methods In total, 24 female Balb/c mice were randomized to normal control (group A), asthma control (group B), and M. vaccae nebulization (group C) groups. Both groups B and C were sensitized using ovalbumin for establishment of the asthmatic model; group A received phosphate-buffered solution. Prior to the establishment of asthma, Group C was nebulized with M. vaccae. Airway responsiveness was measured in all the groups, using a noninvasive lung function machine before and 24 h after establishment of the asthmatic model. The animals were then harvested, and bronchoalveolar lavage fluid (BALF) and lung tissue were collected. The total cell counts in BALF was estimated. Protein expression of TGF-β1, TβR1, Smad1, and Smad7 was detected by immunohistochemistry. The population of CD3 + γδT, IL-13 + CD3 + T, TGF-β + CD3 + T, IL-13 + CD3 + γδT, and TGF-β+ CD3+ γδT cells were detected by flow cytometry. One-way analysis of variance for within-group comparisons, the least significant difference t-test or Student–Newman–Keuls test for intergroup comparisons, and the nonparametric rank sum test for analysis of airway inflammation scores were used in the study. Results The eosinophil count; protein expression of TGF-β1, TβR1, and Smad1; and percentages of CD3 + γδT and IL-13 + CD3 + T cells were significantly lower in the M. vaccae nebulization group than in the asthma control group (P < 0.01). There were significant intergroup differences in the percentages of TGF-β + CD3 + T and IL-13 + CD3 + γδT cells (P < 0.05). Conclusions Mycobacterium vaccae nebulization could confer protection against allergic bronchial asthma by reducing airway responsiveness and alleviating airway inflammation in mice. The underlying mechanism might be attributed its effect on the deregulated expression of TGF-β1, TβR1, Smad1, and Smad7 of the TGF-β/Smad signal transduction pathway.